The effects of a water polo game on the blood redox status of male water polo players - Petridis, L.; Jamurtas, A. Z.; Veskoukis, A.; Kouretas, D. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The purpose of this study was to examine the effects of a real water polo game on the oxidative stress and antioxidants markers of male water polo players. The importance of this study is that it is the first to examine the oxidative stress and antioxidants markers after a water polo game, considering the specific and high demands of the latter. Methods: Twelve players (25.8±3.7 years) were assessed from two teams. The oxidative stress and antioxidants markers which were measured were TBARS, Protein Carbonyls, GSH and GSSG, Total Antioxidant Capacity (TAC) and Catalase. Results: An increase was found after the game for TBARS, for catalase, for GSH, and GSSG. Protein Carbonyls, TAC and the GSH/GSSG ratio did not change significantly. Conclusion: The water polo game was found to be a strong stimulus for oxidative stress, while alterations seem to appear for the antioxidant capability, as indicated by increase of catalase and GSH. The increase of the latter is controversial to the usual effect post exercise. A possible explanation for this effect could be the activation of GSH synthesis in order to meet the increased needs for antioxidant protection. Also, it should be considered that blood samples were taken 10-20 min. after the game, so it is possible that in well-trained subjects, this time period is enough for the conversion of GSSG back to GSH. Yet, it can be stated that, despite the enhanced antioxidant defense of the players, oxidative stress could not be prevented.